2020
DOI: 10.1002/jgc4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐to‐consumer genetic testing companies tell their customers to ‘see a genetic counselor'. How do genetic counselors feel about direct‐to‐consumer genetic testing?

Abstract: Professional societies, the FDA, and many direct‐to‐consumer genetic testing (DTC‐GT) companies have highlighted the value of counseling from a medical professional with genetics expertise in order to enhance the value and minimize the risks associated with DTC‐GT. However, there is limited information available identifying genetic counselors' own views on DTC‐GT, their willingness to counsel consumers based on DTC‐GT results, and their experiences to date seeing DTC‐GT consumers in a clinical setting. We surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 13 publications
3
49
0
Order By: Relevance
“…Fourth, discussions about health risks were less common but focused primarily on submitting DTC-GT generated raw data to third parties for interpretation. Given the level of concern among health care providers about DTC health-related results [22,24,58] and the many studies of individuals' views about these tests [59,60], the level of spontaneous discussion of the test results offered by 23andMe was surprisingly low even after 2017 when that company was once again permitted to offer them. This may be attributable to the limited panel of healthrelated results offered by 23andMe, most of which are relatively uncommon, so that most discussants would not have received a concerning result.…”
Section: Plos Onementioning
confidence: 99%
“…Fourth, discussions about health risks were less common but focused primarily on submitting DTC-GT generated raw data to third parties for interpretation. Given the level of concern among health care providers about DTC health-related results [22,24,58] and the many studies of individuals' views about these tests [59,60], the level of spontaneous discussion of the test results offered by 23andMe was surprisingly low even after 2017 when that company was once again permitted to offer them. This may be attributable to the limited panel of healthrelated results offered by 23andMe, most of which are relatively uncommon, so that most discussants would not have received a concerning result.…”
Section: Plos Onementioning
confidence: 99%
“…While GCs who participated in our study are unified in their practice of ordering confirmatory testing, the selected clinical-grade test varies depending on the proband's cancer history and whether the report was through DTC-GT or TPI services. Prior studies have shown that GCs may not believe they have the professional obligation to be knowledgeable about DTC-GT or feel comfortable interpreting these results (Brett et al, 2012;Hock et al, 2011;Hsieh et al, 2020). Given that the majority of participants in our study believed that it would be easy to provide counseling related to DTC-GT, it appears that GCs have made strides in educating themselves on this topic.…”
Section: Practice Implicationsmentioning
confidence: 78%
“…The findings of a recent study by Hsieh et al (2020) suggest that the majority of genetic counselors have negative attitudes toward DTC-GT, may not believe that these type of results are accurate, and do not think it is appropriate to offer DTC-GT for hereditary cancer predisposition.…”
Section: What Is Known About This Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of DTC testing brought a new category of patients to the medical genetics clinic: individuals seeking genetic counseling services following DTC testing. One study that interviewed practicing genetic counselors in 2016 and 2017 demonstrated that nearly half (40.1%) of surveyed genetic counselors had seen at least one patient for the sole indication of reviewing DTC testing results (41), an increase from the 11% reported in similar studies conducted in 2011 (17). Both the NSGC and the American College of Medical Genetics and Genomics issued position statements on the importance of the availability of genetic counselors to consumers undergoing DTC testing (9,10,61).…”
Section: Roles Of Genetic Counselors In Direct-to-consumer Testingmentioning
confidence: 99%